Seismic response and vulnerability of housing construction types in Klang Valley area - Azlan Adnan; Aminaton Marto; Tuan Norhayati Tuan Chik; Bahiah Baharudin; Structural Engineers World Congress (2002: Yokohama, Japan) (Skudai : Universiti Teknologi Malaysia, 2002)
03